A systematic review and meta-analysis: tailoring asthma treatment on eosinophilic markers (exhaled nitric oxide or sputum eosinophils). Issue 3 (11th October 2010) - Petsky, H L; Cates, C J; Lasserson, T J; Li, A M; Turner, C; Kynaston, J A; Chang, A B
Abstract : Asthma severity and control can be measured both subjectively and objectively. Traditionally asthma treatments have been individualised using symptoms and spirometry/peak flow. Increasingly treatment tailored in accordance with inflammatory markers (sputum eosinophil counts or fractional exhaled nitric oxide (FeNO) data) is advocated as an alternative strategy. The objective of this review was to evaluate the efficacy of tailoring asthma interventions based on inflammatory markers (sputum analysis and FeNO) in comparison with clinical symptoms (with or without spirometry/peak flow) for asthma-related outcomes in children and adults. Cochrane Airways Group Specialised Register of Trials, the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, EMBASE and reference lists of articles were searched. The last searches were in February 2009. All randomised controlled comparisons of adjustment of asthma treatment based on sputum analysis or FeNO compared with traditional methods (primarily clinical symptoms and spirometry/peak flow) were selected. Results of searches were reviewed against predetermined criteria for inclusion. Relevant studies were selected, assessed and data extracted independently by at least two people. The trial authors were contacted for further information. Data were analysed as 'intervention received' and sensitivity analyses performed. Six (2 adults and 4 children/adolescent) studies utilising FeNO and three adult studies utilising sputum eosinophils were included. These studies had a degree of clinical heterogeneity including definition of asthma exacerbations, duration of study and variations in cut-off levels for percentage of sputum eosinophils and FeNO to alter management in each study. Adults who had treatment adjusted according to sputum eosinophils had a reduced number of exacerbations compared with the control group (52 vs 77 patients with ≥1 exacerbation in the study period; p=0.0006). There was no significant difference in exacerbations between groups for FeNO compared with controls. The daily dose of inhaled corticosteroids at the end of the study was decreased in adults whose treatment was based on FeNO in comparison with the control group (mean difference −450.03 μg, 95% CI −676.73 to −223.34; p<0.0001). However, children who had treatment adjusted according to FeNO had an increase in their mean daily dose of inhaled corticosteroids (mean difference 140.18 μg, 95% CI 28.94 to 251.42; p=0.014). It was concluded that tailoring of asthma treatment based on sputum eosinophils is effective in decreasing asthma exacerbations. However, tailoring of asthma treatment based on FeNO levels has not been shown to be effective in improving asthma outcomes in children and adults. At present, there is insufficient justification to advocate the routine use of either sputum analysis (due to technical expertise required) or FeNO in everyday clinical practice.